Distortion of Meaning in Interpretation: A Study of Al-Dakhil in the Rules of Lafaz - Arofatul Mukarromah; M. Havy Sa'dullah; Rima Syahiroh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to examine the phenomenon of al-dakhil, or the infiltration of foreign elements into the interpretation of the Qur’an, which can cause distortion of meaning. The main issue addressed is how al-dakhil emerges in exegesis and the factors that trigger the introduction of external elements such as weak data, isra’iliyyat, and the personal biases of the exegete, thereby risking deviation from the original meaning of the revelation. The approach used is a qualitative method with descriptive analysis, examining tafsir texts and ushul al-tafsir literature in depth to identify forms of al-dakhil related to linguistic rules, as well as analysing their causal factors. The research findings indicate that al-dakhil often arises due to insufficient mastery of the Arabic language, group fanaticism, and the influence of ideology and invalid scientific data. An important conclusion is that this study underscores the necessity of linguistic literacy, critical evaluation of sources, and the strict application of linguistic rules in the tafsir process to preserve the authenticity and validity of the Qur’an’s meaning. The main implication is the importance of strengthening responsible and scientific exegesis methodologies to prevent the introduction of foreign elements that distort the meaning of revelation.